Efficacy and safety of deferasirox estimated by serum ferritin and labile plasma iron levels in patients with aplastic anemia, myelodysplastic syndrome, or acute myeloid leukemia with transfusional iron overload - Kim, Il-Hwan; Moon, Joon-Ho; Lim, Sung-Nam; Sohn, Sang-Kyun; Kim, Hoon-Gu; Lee, Gyeong-Won; Kim, Yang-Soo; Lee, Ho-Sup; Kwon, Ki-Young; Kim, Sung-Hyun; Park, Kyung-Tae; Chung, Joo-Seop; et al. (Transfusion (Philadelphia, Pa.), 2015)
BACKGROUND Patients receiving red blood cell (RBC) transfusions are at risk of iron overload, which can cause significant organ damage and is an important cause of morbidity and mortality. STUDY DESIGN AND METHODS This study was an open‐label, single‐arm, prospective clinical study to evaluate the efficacy and safety of deferasirox (DFX) in patients with aplastic anemia (AA), myelodysplastic syndrome (MDS), or acute myeloid leukemia (AML). Patients with serum ferritin levels of at least 1000 ng/mL and ongoing transfusion requirements were enrolled. DFX was administered for up to 1 year. A total of 100 patients were enrolled. RESULTS Serum ferritin levels decreased significantly following treatment (from 2000 to 1650 ng/mL, p = 0.004). The median absolute reduction in serum ferritin levels was −65 ng/mL in AA (p = 0.037), −647 ng/mL in lower‐risk MDS (MDS‐LR; p = 0.007), and −552 ng/mL in higher‐risk MDS (MDS‐HR)/AML (p = 0.482). Mean labile plasma iron (LPI) levels decreased from 0.24 μmol/L at baseline to 0.03 μmol/L at 1 year in all patients (p = 0.036). The mean LPI reduction in each group was −0.17 μmol/L in AA, −0.21 μmol/L in MDS‐LR, and −0.30 μmol/L in MDS‐HR/AML. Gastrointestinal disorders were commonly observed among groups (16.0%). DFX was temporarily skipped for adverse events in seven patients (7.0%) and was permanently discontinued in 11 patients (11.0%). CONCLUSION DFX reduced serum ferritin and LPI levels in patients with transfusional iron overload. Despite the relatively high percentage of gastrointestinal side effects, DFX was tolerable in all subgroups.